Epigenetic Mechanisms in Development and Disease. (23rd May 2013) - Murrell, Adele; Hurd, Paul J.; Wood, Ian C.
Abstract : Our advances in technology allow us to sequence DNA to uncover genetic differences not only between individuals, but also between normal and diseased cells within an individual. However, there is still a lot we have yet to understand regarding the epigenetic mechanisms that also contribute to our individuality and to disease. The 80th Biochemical Society Annual Symposium entitled Epigenetic Mechanisms in Development and Disease brought together some leading researchers in the field who discussed their latest insights into epigenetic mechanisms. Methylation of DNA has been the focus of much study from both a developmental perspective and imprinting of genes to its contribution to diseases such as cancer. Recently, the modification of methylcytosine to hydoxymethylcytosine within cells was uncovered, which opened a host of potential new mechanisms, and a flurry of new studies are underway to uncover its significance. Epigenetics is not confined to a study of DNA, and the post-translational modifications on the histone proteins have a significant role to play in regulating gene expression. There are many different modifications and, as shown at the Symposium, new variations used by cells are still being uncovered. We are some way to identifying how these modifications are added and removed and the protein complexes responsible for these changes. A focus on the function of the complexes and the interactions between individual modifications to regulate gene expression is advancing our knowledge, as discussed in the accompanying papers, although there are clearly plenty of opportunities for new breakthroughs to be made.